STUDY ON THE CONSTRUCTION OF EARLY MATHEMATICAL CONCEPTS INVOLVING VISUALLY IMPAIRED STUDENTS AND ASSISTIVE TECHNOLOGY - Raupp Sganzerla, Maria Adelina; Geller, Marlise (Revista Inclusiones, 2020)
Inclusive Education in Brazil guarantees that all students have equal conditions to access school enrollment. In this context, visual impairment is one of the disabilitiesfound in school reality. This article presents an excerpt from a doctoral investigation to reflect on the process of blind and/or low vision students’ construction of earlymathematical concepts with the use of Assistive Technology (AT). From a qualitative approach, the research was founded on the Discursive Textual Analysis, based on observations and interventions carried out during the attendance offive elementary school studentsby the Specialized Educational Service (SES). This work reports the different stages the participantsunderwent to understand themathematical concepts that involve counting, recognition of quantities, numerical symbols, besides basic mathematical operations. The results suggestthat visually impaired childrenhavethe same potential as sighted childrenconcerningthe construction of the concept of number. However, it is essential to use ATsand adapted materials to make this concept effective.